Profesionalisme Guru dalam Perspektif Undang-Undang Nomor 14 Tahun 2005 dan Kitab Tadzkirah Al-Sami’ wa al-Mutakallim: Studi Analisis Komparatif - Supriyono, Supriyono; Khoerudin, Koko (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
The development of national education requires Islamic Religious Education (IRE) teachers who are not only legally and academically competent but also ethically and spiritually grounded. This study analyzes the concept of teacher professionalism through a comparative content analysis between Law No. 14 of 2005 on Teachers and Lecturers and the classical Islamic ethical perspective in Tadzkirah Al-Sami’ wa al-Mutakallim by Badruddin Ibn Jama’ah. Using a library research design with qualitative content analysis, the study identifies two primary dimensions of professionalism: (1) formal-legal competence, encompassing pedagogical, professional, social, and personality standards as mandated by the law; and (2) moral-spiritual integrity, emphasizing sincerity (ikhlas), adab, humility, and ethical responsibility as articulated in the classical text. The analysis results in a dual-dimension professionalism model that integrates legal compliance with ethical internalization, forming a legal-ethical integrative framework for IRE teacher development. This model demonstrates that holistic professionalism requires the alignment of technical competence, regulatory standards, and inner moral formation. The study contributes theoretically by offering a structured synthesis between modern legal frameworks and classical Islamic educational ethics in shaping contemporary IRE teacher professionalism.